Mampukah Kebijakan Deviden Sebagai Variabel Intervening? - Eny Maryanti; Ruci Arizanda Rahayu; Saniyah Kholidiyah (Universitas Muhammadiyah Malang, 2022)
This study aims to examine the effect of Profitability, Leverage, and Ownership Structure on Firm Value with Dividend Policy as Intervening Variables. This research method uses a quantitative research method with secondary data sources in the form of financial reports and annual reports of Food and Beverage Companies listed on the IDX for 2017-2020. Sample selection was carried out using the purposive sampling method and 13 sample companies that met the criteria. The data analysis technique in this study used Eviews 12. The research results show that (1) Profitability has an effect on Dividend Policy (2) Leverage has no effect on Dividend Policy (3) Ownership Structure has no effect on Dividend Policy (4) Profitability has an effect on Firm Value (5) Leverage has no effect on Firm Value ( 6) Dividend Policy has an effect on Firm Value (7) Ownership Structure has no effect on Firm Value (8) Dividend Policy is able to mediate the influence of Profitability on Firm Value (9) Dividend Policy is not able to mediate the influence of Leverage on Firm Value (10) Dividend Policy has no effect mediate the effect of Ownership Structure on Firm Value. Dividend policy can increase or decrease the value of the company when profitability is high or not. Dividend policy cannot increase or decrease the value of the company when leverage and ownership structure are high or not. This empirical study contributes to practice in companies in making policies and becomes a reference for investors in making investment decisions.